STUDENTS PERCEPTIONS ON IMPLEMENTATION OF LEARNING PROCESS IN THE DEPARTMENT OF CIVIL ENGINEERING STATE UNIVERSITY OF PADANG ON SEMESTER JANUARY-JUNE 2014 - 521-528 , M. Abdullah (Universitas Negeri Padang, 2015)
Abstract This research was motivated by the fact that there are many students who repeat courses in semester January-June and not seriously to present the learning process. This is a descriptive research which aims to reveal students' perceptions on the implementation of learning process in the Department of Civil Engineering, State University of Padang, in semester January-June 2014. The population was all students of S1 and D3 actively taking courses in the Department of Civil Engineering in semester January–June 2014. Samples were taken purposively by using Slovin formula with 82 students samples of S1 and 76 students samples of D3. The research data were obtained from questionnaires that given to students, and then analyzed with percentage technique. The results showed that D3 students' perceptions on the learning process in term of student assessment on the lecture material are very good, students assessment on the lecturer is very good, student assessment on the presentation of the material is good, and student discipline classroom assessment is good. S1 students' perceptions on the learning process in terms of student assessmenton the lecture material is very good, students assessment on the lecturer is very good, student assessment on the presentation of the material is good, and student discipline classroom assessment is good. This research recommended for lectures to work more variance and interesting on learning process to students , that makes students have more spirits to present the learning process because a little bit bad perceptions from students should be get respons from lectures in Department Of Civil Engineering subject. Keywords: Perceptions, Learning process, The Department of Civil Engineering